Analisis kualitas pembelajaran matematika pada penggunaan platform google classroom materi kombinatorika - Mustika, Helma; Nadela, Junita (Mahesa Research Center, 2021)
Using the background of the problem is this research is the lack of knowledge of theachers and students about how use the application Google Classroom (GC) in learning activities, but there are still students do not have google account to log in the application GC. This research is a descriptive qualiative research. This study aims to determine how the quality of mathematics learning in the use of the application GC of combinatorics material for class XII IPA students of SMA Negeri 1 Pasir Penyu. The subjects of this study were selected based on the student’s daily test scores on combinatoric material using the application GC, where the subjects of this study included six students of class XII IPA 3 consisting of two students who had high test scores, two students who had mean test scores and two students who had low test scores. Data collection techniques are interview guidelines and questinnaire sheets. Furthermore, the data obtained will be analyzed based on indicators of the quality of mathematics learning. Data analyzed techniques in this study were data reduction, data presentation, and data verification. Based on the final results of the questionnaire sheets scores and the average posttest so that the average of both is 71,5 whit good categories, it can be concluded that the quality of mathematics learning in the use of the application GC of combinatorics material for class XII IPA 3 students of SMA Negeri 1 Pasir Penyu is good.